Classification of TP53 mutations and HPV predict survival in advanced larynx cancer. (27th June 2016) - Scheel, Adam; Bellile, Emily; McHugh, Jonathan B.; Walline, Heather M.; Prince, Mark E.; Urba, Susan; Wolf, Gregory T.; Eisbruch, Avraham; Worden, Francis; Carey, Thomas E.; Bradford, Carol
Abstract : Objectives/Hypothesis: Assess tumor suppressor p53 ( TP53 ) functional mutations in the context of other biomarkers in advanced larynx cancer. Study Design: Prospective analysis of pretreatment tumor TP53, human papillomavirus (HPV), Bcl‐xL, and cyclin D1 status in stage III and IV larynx cancer patients in a clinical trial. Methods: TP53 exons 4 through 9 from 58 tumors were sequenced. Mutations were grouped using three classifications based on their expected function. Each functional group was analyzed for response to induction chemotherapy, time to surgery, survival, HPV status, p16INK4a, Bcl‐xl, and cyclin D1 expression. Results: TP53 mutations were found in 22 of 58 (37.9%) patients with advanced larynx cancer, including missense mutations in 13 of 58 (22.4%) patients, nonsense mutations in four of 58 (6.9%), and deletions in five of 58 (8.6%). High‐risk HPV was found in 20 of 52 (38.5%) tumors. A classification based on Evolutionary Action score of p53 (EAp53) distinguished missense mutations with high risk for decreased survival from low‐risk mutations ( P = 0.0315). A model including this TP53 classification, HPV status, cyclin D1, and Bcl‐xL staining significantly predicts survival ( P = 0.0017). Conclusion: EAp53 functional classification of TP53 mutants and biomarkers predict survival in advanced larynx cancer. Level of Evidence: NA. Laryngoscope, 126:E292–E299, 2016